Fundamental nursing care in patients with the SARS-CoV-2 virus: results from the ‘COVID-NURSE’ mixed methods survey into nurses’ experiences of missed care and barriers to care - Holly V. R. Sugg (BMC, 2021)
Abstract Background Patient experience of nursing care is associated with safety, care quality, treatment outcomes, costs and service use. Effective nursing care includes meeting patients’ fundamental physical, relational and psychosocial needs, which may be compromised by the challenges of SARS-CoV-2. No evidence-based nursing guidelines exist for patients with SARS-CoV-2. We report work to develop such a guideline. Our aim was to identify views and experiences of nursing staff on necessary nursing care for inpatients with SARS-CoV-2 (not invasively ventilated) that is omitted or delayed (missed care) and any barriers to this care. Methods We conducted an online mixed methods survey structured according to the Fundamentals of Care Framework. We recruited a convenience sample of UK-based nursing staff who had nursed inpatients with SARS-CoV-2 not invasively ventilated. We asked respondents to rate how well they were able to meet the needs of SARS-CoV-2 patients, compared to non-SARS-CoV-2 patients, in 15 care categories; select from a list of barriers to care; and describe examples of missed care and barriers to care. We analysed quantitative data descriptively and qualitative data using Framework Analysis, integrating data in side-by-side comparison tables. Results Of 1062 respondents, the majority rated mobility, talking and listening, non-verbal communication, communicating with significant others, and emotional wellbeing as worse for patients with SARS-CoV-2. Eight barriers were ranked within the top five in at least one of the three care areas. These were (in rank order): wearing Personal Protective Equipment, the severity of patients’ conditions, inability to take items in and out of isolation rooms without donning and doffing Personal Protective Equipment, lack of time to spend with patients, lack of presence from specialised services e.g. physiotherapists, lack of knowledge about SARS-CoV-2, insufficient stock, and reluctance to spend time with patients for fear of catching SARS-CoV-2. Conclusions Our respondents identified nursing care areas likely to be missed for patients with SARS-CoV-2, and barriers to delivering care. We are currently evaluating a guideline of nursing strategies to address these barriers, which are unlikely to be exclusive to this pandemic or the environments represented by our respondents. Our results should, therefore, be incorporated into global pandemic planning.